2019
DOI: 10.1111/php.13151
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Intensity Blue Light on Fusobacterium nucleatum Membrane Integrity

Abstract: Oral malodour is considered to be caused mainly by the production of volatile sulfide compounds (VSC) by anaerobic gram‐negative oral bacteria. Previous studies showed that these bacteria were susceptible to blue light phototoxicity mediated by the production of reactive oxygen species (ROS). In the present study, we tested the effect of blue light on the integrity Fusobacterium nucleatum's membrane, cellular proteins and DNA. Bacterial samples were exposed to high intensity blue light for 0, 70, 140 and 280 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Previously, we have shown that exposing bacterial cells to a sub-lethal dosage of blue light increases their cell membrane permeability [9,11], and this suggested that this effect may increase the efficacy of antibacterial agents. In this study, we examined the combined effect of sub-lethal blue light and sodium fluoride on the cariogenicity of Streptococcus mutans in a biofilm configuration.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, we have shown that exposing bacterial cells to a sub-lethal dosage of blue light increases their cell membrane permeability [9,11], and this suggested that this effect may increase the efficacy of antibacterial agents. In this study, we examined the combined effect of sub-lethal blue light and sodium fluoride on the cariogenicity of Streptococcus mutans in a biofilm configuration.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies showed that sub-lethal dosage of blue light can increase cell membrane permeability in Fusobacterium nucleatum [13,14] and suggested that this effect was mediated through the production of reactive oxygen species [11]. In the present study, we tested the combined effect of sub-lethal blue light and silver nanoparticles on the ability of Fusobacterium nucleatum to produce malodor, its cell membrane integrity, and measured the levels of ROS produced following this treatment in order to understand the mechanism for the combined phototoxic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the phototoxic effect of blue light against malodor producing bacteria [10] with or without the added effect of photosensitizers [11] or photoactivators [12]. Furthermore, the main antibacterial mechanism of blue light against Fusobacterium nucleatum was shown to be membrane damage [13] that could be leveraged to increase the efficacy of other antibacterial agents [14]. The aim of the present study was to test the added effect of silver nanoparticles on blue light phototoxicity against Fusobacterium nucleatum.…”
Section: Introductionmentioning
confidence: 93%
“…Previously, we showed that sublethal dosage of blue light can increase cell membrane permeability in Fusobacterium nucleatum (10). We postulated that this effect may increase the efficacy of other antibacterial agents.…”
Section: Discussionmentioning
confidence: 99%